The investigation and prevalence of pulmonary embolism among emergency department patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD): A multi-centered linked administrative database study - Brian H. Rowe; Esther H. Yang; Cristina Villa-Roel; Bo Zheng; Irvin Mayers (PLoS ONE, 2026)
Background Although patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) may be investigated for pulmonary embolism (PE) in the emergency department (ED), little is known about the prevalence of PE and factors associated with investigation. We sought to evaluate the PE prevalence among patients presenting to the ED with AECOPD. Methods All adult patients presenting with AECOPD to six EDs between January 2015 and June 2021 using ICD-10-CA codes from administrative data. The primary outcomes were the investigation for and prevalence of PE. Conventional, age-adjusted D-dimer (AADD) and chest imaging are reported. A multivariable logistic regression was used to identify predictors of investigations for PE among patients with AECOPD, including demographic characteristics, comorbidities, and ED presentation data as covariates. Results Of the 25,510 patients with AECOPD, 12,164 (48%) patients (median age 70 years, 50% males, 46% hospitalized) were included after applying exclusion criteria. Overall, 2,072 (17%) patients received at least one test for PE: 84% had a D-dimer, 44% had a chest CT and 2% had lung scans. Overall, 68 (0.5%) patients received a diagnosis of PE; 41 (0.3%) received a PE co-diagnosis in the ED and 27 (0.2%) patients received a primary PE diagnosis while hospitalized. Use of an AADD could reduce CT image ordering by approximately 13%. Overall, 852 (7%) returned to the ED and 490 (4%) died within 30 days. The presence of chest pain (aOR=2.71; 95% CI: 2.24–3.28) and cough/congestion (aOR=0.57; 95% CI: 0.46–0.70) increased and decreased PE investigations, respectively. Conclusion The overall prevalence of PE among patients presenting to the ED with AECOPD was low (less than 1%). While acknowledging PE may occur concurrently with AECOPD, clinicians should be cautious to avoid over-investigation, which has a negative impact on operational flow, increases costs, and may be harmful to patients. Evidence-based pathways using information readily available at presentation and selective investigations (e.g., decision rules and AADD cut-offs) have the potential to improve resource use and facilitate shared decision-making in the acute setting.